2013
DOI: 10.4995/wrs.2013.1240
|View full text |Cite
|
Sign up to set email alerts
|

Breeding programmes to improve male reproductive performance and efficiency of insemination dose production in paternal lines: feasibility and limitations

Abstract: This paper reviews the current genetic knowledge on issues related with the efficient use of bucks in artificial insemination (AI). Differences between lines have been found to be relevant in semen production and quality traits not necessarily related to their specialisation as maternal or paternal lines. Accurate heritability estimates indicate that genetic selection to increase semen production by improving male libido and/or reducing the number of rejected ejaculates may not be effective. However, total spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…In pigs, Broekhuijse et al (2011) obtained significant (P < 0.05) effects of progressive motility, curvilinear velocity and beat cross frequency on the farrowing rate. Although the presence of gel plugs in the semen is a major criterion for ejaculate rejection in some AI centres (Piles et al, 2013), our results revealed that this characteristic has no effect on either fertility or prolificacy. We did not find any information in the literature on this subject and this result therefore appears to be original.…”
Section: Means and Variations Of Reproductive Performancescontrasting
confidence: 55%
See 1 more Smart Citation
“…In pigs, Broekhuijse et al (2011) obtained significant (P < 0.05) effects of progressive motility, curvilinear velocity and beat cross frequency on the farrowing rate. Although the presence of gel plugs in the semen is a major criterion for ejaculate rejection in some AI centres (Piles et al, 2013), our results revealed that this characteristic has no effect on either fertility or prolificacy. We did not find any information in the literature on this subject and this result therefore appears to be original.…”
Section: Means and Variations Of Reproductive Performancescontrasting
confidence: 55%
“…In commercial rabbit farms, heterospermic pools that are prepared in rabbit insemination centres are usually used for insemination, whereas breeders practice homospermic inseminations for genetic improvement. In rabbit, it is generally assumed that the male contribution to fertility after AI with high-concentration semen doses is negligible (Piles, 2013), but it could be higher in more restrictive AI conditions. Studies of the relationships between semen characteristics and fertilising ability can be classified into two categories.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was actually based on the analytical findings of the seminal samples collected once a week from rabbit bucks fed on ration treated with soybean and sunflower oils. According to Castellini and Lattaioli (1999), estimating semen quality is important in determining the reproductive efficiency in rabbit bucks, where it has been documented to be correlated with sperm fertilizing ability (Castellini et al, 2000;Brun et al, 2002;Hagen et al, 2002;Castellini, 2007;Piles et al, 2013;Theau-Clément et al, 2016). The present data indicated that semen collected from rabbit bucks supplemented with vegetable oils had higher sperm concentration, total sperm output, percentage of motile sperms, as well as lower percentages of dead and altered acrosomal sperms than the control bucks.…”
Section: Discussionsupporting
confidence: 51%
“…With AI, the impact of reproductive performance (i.e. male contribution to fertility and prolificacy) of individual males is vital (Piles et al, 2013).…”
Section: Importance Of Rabbit Buck In Reproductionmentioning
confidence: 99%
“…Many factors influence the production and quality of rabbit semen such as the genetic origin (growth lines have worse seminal qualities and fertility rates than maternal lines) , the season Theau-Clément et al, 2015), the photoperiod (Roca et al, 2005; and the collection frequency . The production of fertile doses is determined by several components: i) male libido and characteristics of the ejaculate which form part of the criterion for ejaculate rejection; ii) volume and sperm concentration of the ejaculate (determining the amount of doses that can be obtained); and iii) the quality of sperm (determining the minimum sperm dosage required to ensure fertilization) (Piles et al, 2013). Subjective estimation of motility and evaluation of sperm morphology are the two laboratory assays most widely used for the rabbit semen evaluation in insemination centers .…”
Section: Importance Of Rabbit Buck In Reproductionmentioning
confidence: 99%